إسهامات الشيخ محمد علي آدم الإثيوبي في خدمة السنة النبوية –عرض ودراسة - رمضاني, محمد; لعرج, بلال (جامعة الوادي - University of Eloued, 2023)
الحمد لله والصلاة والسلام على رسول الله، أما بعد: فهذا ملخص للبحث الذي يحمل عنوان: ((إسهامات الشيخ محمد علي آدم الإثيوبي في خدمة السنة النبوية)) وهو بحث مختصر في بيان اسهامات وجهود أحد الاعلام المعاصين والمحدثين المعتبرين في خدمة السنة النبوية على صاحبها أزكى الصلاة والتسليم، وهو الشيخ محمد علي بن آدم الاثيوبي، ولأنه علم معاصر فقد قلَّ الکلام في ترجمته، وقلَّت المصنفات حول إسهاماته وجهوده، رغم منزلته العلمية وما قدمه للأمة من كتب نافعة في شتى علوم الحديث، ودروس ماتعة، منها جملة طيبة في علوم الحديث، ولهذا يحتاج الباحث أن يتعرف على هذا العلم ويقف على آثاره في علم الحديث ويعرف إسهاماته في خدمة السنة وأبرز مميزات ومعالم جهوده وإسهاماته. Summary Praise be to God, and peace and blessings be upon the Messenger of God, but after: This is a summary of the research entitled: ((The contributions of Sheikh Muhammad Ali Adam, the Ethiopian in the service of the Prophet’s Sunnah)), which is a brief research in explaining the contributions and efforts of one of the contemporary scholars considered in the service of the Prophet’s Sunnah to its owner, the best of prayer and delivery, which is Sheikh Muhammad Ali bin Adam Al -Ethiopi And because it is a contemporary science, the words have decreased in its translation, and the works have diminished about his contributions and efforts, despite his scientific status and the beneficial books he presented to the nation in various sciences of hadith and lessons of good, including a good sentence in the various sciences of hadith, and for this the researcher needs to know this scholar and stand on its effects in the science The conversation knows his contributions to the service of the Sunnah and the most prominent features and features of his efforts and contributions. ا
مقال
Keywords: محمد علي الاتيوبي – السنة النبوية – إسهامات – خدمة; Keywords: Sheikh Muhammad Ali Adam, the Ethiopian- Prophet’s Sunnah- The contributions- the service.